Rencana Bisnis (Business Plan) : Jasa Content Creator - Abdi Ramadhan; Eddy Supriyatna (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
"Business Planning Content Creator Services" is a business plan that offers services in the creative industries. With the rapid development of social media in this digital age, we can see a potential opportunity to plan a content creator service business, which includes several service components, namely photography, videography, design, copywriting, social media handling, and creative ideas for projects. This business plan aims to create a new business plan in the creative industries engaged in services and create opportunities to be able to generate profitable profits. Based on the results of the analysis and discussion, it can be concluded that this business is feasible to be realized on the basis of considerations, among others, because the market potential of the content creator services business increases with the increasing use of social media in Indonesia. This business financial planning also shows that this business will provide profit and deserve to be realized. Financial analysis which consists of Payback Period and Break Event Point (BEP) requires a fairly short estimated time of 2 years 3 months, the Net Present Value (NPV) value of Rp. 291,120,221.5, - this shows that this investment can be profitable and profitable, and the Internal Rate of Return (IRR) of 81% means higher than the interest rate.